Incidence of hypotension in lower segment Caesarean section - a comparison of intrathecal Fentanyl- Bupivacaine combination with Bupivacaine alone - Paudel, Bandana; Gautam, Sanjay; Paudel, Sumitra; Poudyal, Shailesh (Birat Journal of Health Sciences, 2024)
Introduction: After subarachnoid block with conventional heavy Bupivacaine, hypotension is the most common complication and is caused by decrease in systemic vascular resistance and/or cardiac output. Even with standard doses of the drug for parturient, there are evidences of severe hypotension and other complications despite adequate analgesia and anaesthesia. Adjuvants are used to enhance the quality of blocks with less complications.Objectives: It was to evaluate the effectiveness of combining bupivacaine and fentanyl for spinal anesthesia during lower segment Caesarean section (LSCS) as opposed to using bupivacaine alone for the incidence of hypotension.Methodology: This is a prospective study of 210 patients aged 18-35 years of American society of Anesthesiologists Physical Status II undergoing elective lower segment Caesarean section, randomly assigned to two groups: Group A, received a mixture of intrathecal 2ml of 0.5% Bupivacaine and 10 mcg Fentanyl(2.2ml) and Group B, received only 2.2 ml of Bupivacaine. Noninvasive blood pressure was checked at 1,2,4,6,10,20,40 and 60 min after subarachnoid block and then post-surgery.Results: The occurrence of hypotension was higher in Group B (26.6%) compared to Group A (8.6%). Conclusion: Our study suggests that the intrathecal Fentanyl-Bupivacaine combination is effective in reducing the incidence of hypotension after SAB for elective LSCS. Additional research is needed to determine this combination’s optimal dosage and timing.